Prevalence of sleep disorders in Parkinson’s disease patients in two neurology referral hospitals in Ethiopia - Melka, Dereje (BMC Neurol, 2019)
BACKGROUND: Non motor symptoms (NMS) of Parkinson’s disease (PD) are common and can be more disabling than motor symptoms. Sleep disorders can be seen in up to 98% of patients with Parkinson disease. Poor sleep quality has been associated with poverty and race, and yet there has been no prior report on sleep disorders in those with PD living in sub Saharan Africa. We wished to document the prevalence of sleep disorders in PD patients in Ethiopia. METHODS: We conducted a cross-sectional point prevalence study from July 1 to October 30, 2015 of all patients attending the neurology outpatient department in Tikur Anbessa and Zewuditu Memorial Hospitals, Addis Ababa, Ethiopia. Demographic data, clinical history and physical examination findings were collected from participants using a structured questionnaire. We used the Parkinson’s disease sleep scale version two (PDSS-2) and Epworth Sleepiness Scale (ESS) to assess the sleep symptoms. RESULTS: Of the 155 patients surveyed, all patients reported some sleep problem. Over 43.9% of patients had a PDSS score > 18. The median score of ESS was 9 (IQR = 5–12), with 77/155 (49.7%) of the patients having possible or definite excessive daytime somnolence. A high EDSS score significantly associated with a Hoehn & Yahr score > 4 (p = 0.02). CONCLUSIONS: In Ethiopian PD patients, the prevalence of those with severe sleep disorders is the highest reported to date. The prevalence of possible/definite EDS is amongst the highest in the world. Further investigation into whether poverty or race explains this finding is needed.